Improvisations in classic and modified techniques of flap surgery to improve the success rate for pressure ulcer healing in patients with spinal cord injury. Issue 4 (14th June 2012) - Singh, Roop; Singh, Raghubir; Rohilla, Rajesh K; Magu, Narender K; Goel, Rakesh; Kaur, Kiranpreet
<x xml:space="preserve">Abstract</x> The recurrence of pressure ulcers (PrUs) and dehiscence of reconstructive flap have always been a problem. The present study aimed to evaluate the results of reconstructive flap surgeries in patients with spinal cord injury (SCI) having PrUs, using classic and modified flaps with improvisations to decrease wound dehiscence, flap necrosis and tension in flap. This is a prospective clinical study. The setting was a tertiary care centre in northern India. Thirty‐five patients with SCI having 37 stage III and IV PrUs. PrUs were treated using classic and modified flaps with improvisations. The outcome was evaluated using criteria of wound dehiscence, flap necrosis and recurrence. The results of flap surgery were excellent in 32 (86·48%) patients, good in 4 (10·81%) patients and poor in 1 (2·7%) patient. Partial flap necrosis (2·7%), low incidence of PrU recurrence rate at flap site (5·4%) and overall PrU recurrence (11·4%) were the complications observed. Improvisation of classic and modified techniques of flap surgeries along with reinforcement of general care principles of paraplegia can be effective in minimising complications often associated with PrU reconstructive surgery thus improving the ultimate outcome.